اثر الزواج في توثيق علاقات المغول المحلية الدولية - شارد الركابي صفاء (Journal of College of Education, 2019)
Allah, may He be glorified and exalted, legitimate marriage and make it a means of acquaintance and convergence between people. Nation is a group of families, that interrelated in principles, laws, customs and traditions which their effects vary among nations due to their levels variation of knowledge and culture. Marriage is the pillar of the family; with marriage you can make new relations, its importance is determined by marriage goals. Mongols took the marriage as a means to ensure their future plans and to achieve their ambitions. So the study of such a subject is very important because it reveals to us how their strength grew, since most of their marriages were based on political interests, they make affinity with the powerful tribes. The research included an introduction that included an identification, origin and habitat of Mongols. Then two chapters, first chapter is (marriage effect in the documentation of their relations with Mongols tribes) including Tatars, Qongirats, Keraites, Oriats and Merkits tribe. While the second chapter focused on (marriage effect in the documentation of Mongols’ foreign relations) with Empire of China, Persians, Mamluk Sultanate and Europe.